Performance Advantages and Applications of Carbon Dots in Biological Detection - Peng, Bo (Transactions on Environment, Energy and Earth Sciences, 2026)
Carbon dots (CDs), as zero-dimensional carbon-based nanomaterials, have emerged as a research focus in biomedical fields due to their superior properties compared to traditional fluorescent materials. This paper first outlines the background of CDs, including their discovery timeline and core characteristics such as tunable photoluminescence, nanoscale size, non-toxicity, and good biocompatibility. It then systematically analyzes three key performance advantages of CDs in biological applications: excellent fluorescent properties, such as tunable colors, high stability, red/near-infrared emission, nanoscale size-enabled benefits, such as good water solubility, easy surface functionalization, deep tissue penetration, and non-toxicity  Subsequently, the paper explores specific application scenarios in biological detection, including ion detection, in vitro cell imaging, and in vivo biological imaging. Finally, the paper discusses current challenges and future outlooks, emphasizing that CDs hold great potential to advance clinical diagnosis and life science research with further technological development. In the future, the development of carbon dots will further advance the progress of the biomedical field.
Keywords: Carbon dots; biological detection; fluorescent probes; bioimaging; nanomaterials.